(untitled) - Michaels, Chris Franchetti (Hoboken, N.J, 2012)
The book gives you technique-specific chapters covering: basic metal work, metal cold connections, sculpting with metal clay, embellishing metal, designing with chain, using adhesives, and working with art glaze, resin, and leather. Plus, a final chapter devoted to example projects gives you instruction for making 12 unique pieces to add to your jewelry collection.
Keywords: Jewelry making,Làm đồ trang sức